Structures of Trichloromethyl Thiocyanate, CCl3SCN, in Gaseous and Crystalline State. Issue 10 (10th March 2016) - Berrueta Martínez, Yanina; Rodríguez Pirani, Lucas S.; Erben, Mauricio F.; Boese, Roland; Reuter, Christian G.; Vishnevskiy, Yury V.; Mitzel, Norbert W.; Della Védova, Carlos O.
Abstract: Trichloromethyl thiocyanate, CCl3 SCN, was structurally studied in both the gas and crystal phases by means of gas electron diffraction (GED) and single‐crystal X‐ray diffraction (XRD), respectively. Both experimental studies and quantum chemical calculations indicate a staggered orientation of the CCl3 group relative to the SCN group. This conclusion is supported by the similarity of the C−SCN bond length to that of the anti ‐structure of CH2 ClSCN (Berrueta Martínez et al. Phys. Chem. Chem. Phys . 2015, 17, 15805–15812).1 Bond lengths and angles are similar for gas and crystal CCl3 SCN structures; however, the crystal structure presents different intermolecular interactions. These include halogen and chalcogen type interactions, the geometry of which was studied. Characteristic C‐Y⋅⋅⋅N angles (Y=Cl or S) close to 180° provide evidence for typical σ‐hole interactions along the halogen/chalcogen−carbon bond in N⋅⋅⋅Cl and N⋅⋅⋅S, intermolecular units. Abstract : Crystallize the difference : The crystal and gas‐phase structures of CCl3 SCN are studied by X‐ray and gas electron diffraction techniques. In both phases, the CCl3 group presents a staggered orientation relative to the SCN group. Different intermolecular interactions are detected in the solid phase, including halogen‐ and chalcogen‐type interactions.